Shaheed Bhagat Singh martyrdom day program. - Gadar Memorial Steering Committee; Consulate General of India:::Creator::::::::::::
Poster of program commemorating Shaheed Bhagat Singh Martyrdom Day at Gadar Memorial Hall. Program includes panel discussion, Anand Patwardhan's film "Ram Ke Naam", documentary, and Children's Art Festival. Panelists include Prof. Mrinal Data Chaudhary, Nageshwar Prasad, Shishir Thadani, Ved Prakash Vatur, and moderator Atul Vaidya.